2017
DOI: 10.1128/jvi.01037-17
|View full text |Cite
|
Sign up to set email alerts
|

Mumps Virus SH Protein Inhibits NF-κB Activation by Interacting with Tumor Necrosis Factor Receptor 1, Interleukin-1 Receptor 1, and Toll-Like Receptor 3 Complexes

Abstract: The mumps virus (MuV) small hydrophobic protein (SH) is a type I membrane protein expressed in infected cells. SH has been reported to interfere with innate immunity by inhibiting tumor necrosis factor alpha (TNF-␣)-mediated apoptosis and NF-B activation. To elucidate the underlying mechanism, we generated recombinant MuVs (rMuVs) expressing the SH protein with an N-terminal FLAG epitope or lacking SH expression due to the insertion of three stop codons into the SH gene. Using these viruses, we were able to sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 55 publications
1
19
0
Order By: Relevance
“…Deletion of the SH protein of these viruses did not affect replication and gene expression in vitro (12,14,16,21). Recently, it was reported that MuV SH inhibits TNF-␣, interleukin-1␤ (IL-1␤), and NF-B activation by interacting with TNF receptor 1 (TNF-R1), IL-1 receptor 1 (IL-1R1), and Toll-like receptor 3 (TLR3) complexes (28). These findings suggest the role of SH in evading the host immune response.…”
Section: Discussionmentioning
confidence: 99%
“…Deletion of the SH protein of these viruses did not affect replication and gene expression in vitro (12,14,16,21). Recently, it was reported that MuV SH inhibits TNF-␣, interleukin-1␤ (IL-1␤), and NF-B activation by interacting with TNF receptor 1 (TNF-R1), IL-1 receptor 1 (IL-1R1), and Toll-like receptor 3 (TLR3) complexes (28). These findings suggest the role of SH in evading the host immune response.…”
Section: Discussionmentioning
confidence: 99%
“…HSV1 UL24 binds to NF‐κB subunits p65 and p50 and abrogates nuclear translocation during disease, decreasing NF‐κB activity via the cGAS‐STING response 100. Mumps virus (MuV) small hydrophobic protein (SH) decreases NF‐κB stimulation by reducing inhibitor of kappa B (IκB) kinase α (IKKα) and kinase β (IKKβ), and p65 phosphorylation, including nuclear translocation of p65 in diseased cells 101. HSV1 UL36USP deubiquitinates IκBα and restricts its degradation, subsequently preventing NF‐κB activation during viral infection 102.…”
Section: Regulation Of Innate Immune Responsesmentioning
confidence: 99%
“…Some viruses suppress NF-κB activation to dampen the host immune responses to maintain latency [13] . For example, human bocavirus (HBoV) proteins NS1 and NS1-70 [14] , the mumps virus (MuV) small hydrophobic protein (SH) [15] and Molluscum contagiosum virus (MCV) protein MC005 [16] inhibit TNF-α-mediated activation of NF-κB by reducing the phosphorylation of IKKβ, IκBα, and p65 as well as the translocation of p65 into the nucleus. Some pathogenic microorganisms activate NF-κB for viral gene expression, replication and spread.…”
Section: Introductionmentioning
confidence: 99%